Coup (d'etat) in the Baltic States (1926, 1934): Similarities and Differences - Zenonas Butkus (Lietuvos Istorijos Studijos)
The article compares the political upheaval that took place in Lithuania 80 years ago with those staged in Estonia and Latvia in 1934. Their similarities and differences are discussed, and their historiography is compared. All the three were classified as military-political coups that caused transition from democratic to an authoritarian ruling system without changing socio-economic system or foreign policy. The main alleviating circumstance common to the coups in the Baltics was disproportionate domination of legislative power over the executive in the period after the First World War. The alternatives of power distribution are discussed, employing the Finnish model of democratic system, according to which the parliamentary power is outweighed by the stronger institution of President. The model enabled a more flexible reaction to the danger of extremist trends or serious blows to democracy; it also contributed to the protection from damaging impact of outward influences, which was especially noticeable in Estonia.